Quantitative study on the three-dimensional defense of Puzhuang Suo-Fort ancient wall and the moat - Shenge Shen; Lifeng Tan; Cheng Wang; Pengfei Zhao; Huanjie Liu; Jiayin Zhou; Yinggang Wang; Hong Yuan (PLoS ONE, 2023)
The spatial layout of the coastal forts defense system of the Ming Dynasty of China has been studied in a relatively comprehensive way. Nonetheless, ancient defense mechanisms have not been fully revealed. Previous studies have focused more on the macro and meso levels. Studies into its microscopic construction mechanism need to be enhanced. This research attempts to quantify and validate the rationality of the ancient microscopic defense mechanism, using the ancient defense mechanism of Pu Zhuang Suo-Fort in Zhejiang Province as an instance. This study concentrates on the distribution of firepower strength beyond the walls of coastal defense forts, as well as the effect of wall height on firepower defense capabilities. There is a specific firepower attenuation area near the walls due to the firing blind area in the coastal forts defense system. And the construction of the moat plays an additive role in its defensive capability. Meanwhile, the height of the fort wall will also affect the range of the firing blind zone under Yangmacheng. In theory, there is a reasonable height range of the wall and a proper position of the moat. This height range can meet both good economy and defensive capabilities. In turn, the position of the moats and the height of the walls can verify the rationality of the construction mechanism of the coastal forts’ defense system.